SMART GENERATIVE ALGORITHM (SMART GEN-A): 2D ARCHITECTURAL PHOTO CONVERTER TO BE THE DIGITAL 3D OBJECT - Muhammad Syifa’ul Mufid; Yanu Andy Fredian; Jayadi Jayadi; Nurul Qomariah (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
All objects have various shapes and dimensions. When the three dimensional objects were captured by camera, the output will be two dimensional images although were captured from different angles, this will lead to some misperceptions for observer especially the one never seen the images before. To overcome these misperceptions, it was required a program which is capable of converting a two dimensional image in a digital three dimensional objects. However, conversion process takes a long time without standard measure of real objects to virtual especially for objects with different basic form. The standard is the parametric box with parametric coordinate points to allow creating virtual objects with nearly the exact size of the original. The research uses Rhinoceros 4.0 and Grasshopper to generate the algorithm. The algorithm is designed based on the basic form of object (circle, triangle and square) by using the hierarchy logic of the water gallon. The result is the Smart Generative Algorithm (Smart Gen-A) which can re-create the 2D image into digital 3D and even give the nearly unlimited possible shape for architectural reconstruction.